Sengketa Pemilihan Kepala Desa Antar Waktu Balangka: Abdul Jihar Lawan Panitia Pemilihan - Annurillah, Riksya; Purba, Eugenia Priscilla; Kayla, Syafa Ananda; Rahman, Naziva Azzahra (Media Hukum Indonesia (MHI), 2024)
This research focuses on analyzing the case of Abdul Jihar, a candidate for village head in Labangka District, Sumbawa Regency, East Nusa Tenggara, who was suspected of violating the rules in the Village Head Election. One of the irregularities that occurred was the absence of an election committee and supervisory committee. The aim of this research is to understand the political process and the importance of legal compliance in that context. The results of this study highlight the urgency of community contributions in understanding this issue, including the challenges that exist in village head elections.